Conflict Of Love Of Summer Lyndon In Nora Robert's Table For Two Novel ( 2002 ) An Individual Psychological Approach - Lestari, Sri Puji (2012)
The research investigates how the major character conflict occurs to get his love in Nora Robert's "Table for Two". The study analyzes the novel in terms of its structural elements and based on the individual psychological approach. Structural elements of novel is character and characterization, setting, plot, point of view, style, and theme. The object of the study is the personality of the major character of Summer Lyndon. The data sources are literary data. Those are divided in two categories, primary data sources and secondary data sources. The primary data source is the novel it self. The secondary data some to are books and other sources which support the researcher in analyzing this research. The method of data collection of the study is library research. The technique of data analysis is descriptive analysis. Structural elements of novel is character and characterization, setting, plot, point of view, style, and theme. By adler's Psychological approach is individual psychology is some that attemps to understand to exsperiences and behavior of each person as an organized entity. The outcome of the study shows that the conflict for getting love can change the personality. It is reflected in the major character's personality when she wants to get her love again from her boyfriend.